The Effect of Obstetric Drills Training - Jamaica Core Obstetric Teaching and Training in Emergencies (JOTTIE) on Postpartum Haemorrhage at a Jamaican Teaching Hospital. (February 2022) - Maddan, Cathy; Forbes, Melissa; Campbell-Mitchell, Michelle; Rattray, Carole; Bryan, Lenroy
Objective: To evaluate whether the initiation of JOTTIE, a one day simulation training course focussed on the management of common obstetric emergencies, was associated with a reduction in the morbidity and mortality associated with postpartum haemorrhage (PPH) at the University Hospital of the West Indies (UHWI). Study Design: We conducted a retrospective comparative study that evaluated the incidence of multiple outcomes related to maternal morbidity secondary to PPH, during the two year period immediately prior to the introduction of JOTTIE (pre course arm, N = 88) or the two year period, one year post introduction (post course arm, N = 103) for all women who had vaginal deliveries complicated by PPH at UHWI. A relationship was said to be statistically significant if p < 0.05. Additionally, the study examined risk factors in relation to severity of haemorrhage. Results: Genital tract trauma represented the highest recorded cause of PPH (approximately 71%). The data revealed that patients in the pre training arm were similarly likely to have no adverse outcome in comparison to patients in the post training arm (p = 0.962). There was also no statistically significant relationship between the time period of patient exposure in relation to the JOTTIE course and severity of PPH (p > 0.05). Uterine fibroids and Crohn's disease were the only co-morbidities found to increase the likelihood of severe PPH, at 5.154 times (p = 0.019, OR = 5.154, CI = 1.314-20.212) and 17.848 times (p = 0.085, OR = 17.848, CI = 0.672-474.365), respectively. Conclusions: This study suggests that prior to the introduction of the JOTTIE the rate of maternal morbidity associated with PPH was relatively low at UHWI and there was no significant effect on its management or a significant reduction in maternal morbidity since introduction of the course. Future research on the morbidity related to the other obstetric emergencies addressed at JOTTIE is needed in order to assess the effect of the course as a whole.